Consumer perceptions of food safety in animal source foods choice and consumption in Nairobi’s informal settlements - Bukachi, S.A.; Ngutu, M.; Muthiru, A.W.; Lépine, A.; Kadiyala, S.; Domínguez-Salas, Paula (Springer, 2021)
Background Animal-source foods (ASFs) are high-quality nutrient-dense products key to reducing stunting and micronutrient deficiencies. However, their consumption among the poorest households in urban informal settlements is low. Several drivers beyond price, including health considerations have been reported to drive ASF choice and consumption among consumers. This current study explores consumer perceptions of food safety associated with animal source foods (ASFs) consumption in urban informal settlements with a view to unpacking the health considerations driving their choice and consumption. Methods Coupled households with children 6–59 months formed the study sample. The Food Environments Working Group (FEWG) Framework of the Agriculture and Nutrition for Health academy (ANH) was used to guide the study which utilized qualitative methods namely, 60 in-depth interviews (IDIs), 19 focus group discussions, and 19 key informant interviews (KIIs) complemented by unstructured observations. Data were transcribed and analysed according to emerging themes. Results Consumer perceptions of food safety are driven by concerns about food production, processing, handling, storage and the health risks associated with consumption of the ASFs. For all the ASFs, lack of traceability of source, unhygienic environments in which they were sold and health risks around consuming too much or improperly cooked products were key perceptions from the community. To mitigate against food safety risks, consumers used strategies such as boiling the ASFs, purchasing their products from trusted retailers, avoiding vendors in unhygienic environments and reducing the amount and frequency of consumption of ASFs or totally avoiding their consumption. These consumer perceptions are increasingly influencing the ASFs choice and consumption in low-income populations besides other drivers. Notably, given limited incomes that influence their purchasing power and the need for nutritious diets that included ASFs, the dilemma of quality vis-a-vis quantity persists and consumers still accessed and consumed these ASF products to supplement their diets. Conclusions To enhance food safety for ASFs, as well as assure consumer access to safe ASFs from informal markets, there is need to contextualize the value chain as informed by consumer perceptions on food safety as these influence their ASFs choice and consumption.